The Effectiveness of Preoperative Quadriceps Exercise and Diet Control Program for Older Adults Waiting for Total Knee Arthroplasty: A Randomized Controlled Trial - Rittharomya, Jintana; Aree-ue, Suparb; Malathum, Porntip; Orathai, Pisamai; Belza, Basia; Kawinwonggowit, Viroj (Pacific Rim International Journal of Nursing Research, 2020)
People with knee osteoarthritis often suffer from pain and disability while waiting for total knee arthroplasty.The purpose of this randomized controlled trial study was to determine the effectiveness of the Preoperative Quadriceps Exercise and Diet Control Program on the self-efficacy quadriceps exercise and diet control behavior,body mass index,pain,quadriceps muscle strength,mobility,and health-related quality of life in olderadults on a waitlist for total knee arthroplasty.Ninety-six Thai olderadults were randomly assigned either into an experimental(n=48)or control(n=48)group.The experimental group received the intervention program in addition to standard care, while the control group received only the standard care.Instruments used to collect datawere;Self-Efficacy Expectation Questionnaire, Numeric Pain Rating Scale,Hand-Held Dynamometer,Goniometer,Timed-Up-and-Go Test,Mini-Osteoarthritis of Knee and Hip Quality of Life.Data were analyzed byusing two-way repeated analysis of variance and two-way repeated multivariate analysis of variance. The results revealed that self-efficacy quadriceps exercise and diet control behavior of the experimental group were statistically higher than that in the control group at weeks 2,8and12.The quadriceps muscle strength,range of motion,movement ability,and health-related quality of life of the experimental group were statistically higher whereas pain was statistically lower than those in the control group at weeks 8 and 12,but not significantly different in the body mass index between the two groups.These findings suggest that the program should be recommended for application in nursing practice for older adults waiting for primary total knee arthroplasty.Promoting quadriceps exercise and modifying dietary behavior are independent nurses’roles in enhancing health outcomes in this population.Although pre-operative outcomes are satisfied,a longitudinal effect of the intervention through post-surgery is warranted.